2022
DOI: 10.1029/2021av000546
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Aviation Leads to Increased Ice Crystal Number and a Positive Radiative Effect in Cirrus Clouds

Abstract: Travel restrictions in the wake of the COVID‐19 pandemic resulted in an unprecedented decrease of 73% in global flight mileage in April–May 2020 compared to 2019. Here we examine the CALIPSO satellite observations and find a significant increase in ice crystal number concentrations (Ni) in cirrus clouds in the mid‐latitudes of the Northern Hemisphere, which we attribute to an increase in homogeneous freezing when soot from aircraft emissions is reduced. A relatively small positive global average radiative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Clearly, it is important that the improved process understanding presented here regarding dust‐aviation soot‐cirrus interactions is incorporated into global model parameterizations. Although mineral dust INPs are included in global climate models (Righi et al., 2021; Zhu et al., 2022), predicted aviation soot effects are not discussed in relation to simulated dust and soot particle number concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clearly, it is important that the improved process understanding presented here regarding dust‐aviation soot‐cirrus interactions is incorporated into global model parameterizations. Although mineral dust INPs are included in global climate models (Righi et al., 2021; Zhu et al., 2022), predicted aviation soot effects are not discussed in relation to simulated dust and soot particle number concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the average reduction of homogeneously nucleated ICNCs, which is the basis for the large radiative effect ascribed to aviation soot reductions in Zhu et al (2022), will be overestimated. We recall that for a typical mean updraft speed value σ w = 15 cm s −1 , the reduction in total ICNCs in case Soot relative to case Hom amounts only to 3.5-22.5%, depending on the assumed PSD (Table 2).…”
Section: Aviation-soot Cirrus Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quaas et al (2021) reported that the COVID-19 pandemic related aviation reduction in the Northern Hemisphere leads to a decrease in cirrus cloud cover and reduces the global net-warming radiative forcing. In contrast, Zhu et al (2022) reported a small increase in global radiative forcing because air traffic reduction results in increased cirrus ice crystal number trapping more long-wave radiation in the troposphere. It is suggested that complex and poorly constrained soot-cloud interactions result in inter-model discrepancies and disagreements (Xu et al, 2019).…”
Section: Introductionmentioning
confidence: 93%